Strategy making in a crisis : from analysis to imagination - Gibbert, Michael (Cheltenham, UK. : Edward Elgar, 2010)
'Which strategy making approach works best in a crisis? In current literature, the recommendations oscillate between prediction, control, and practice, but this unique book focuses specifically on strategy making in a crisis.''In a crisis, the business landscape is neither stable nor predictable, resources are scarce rather than abundant, customers disappear and shareholders revolt, all of which can make prediction and control very difficult. Drawing on evidence from philosophy, and on a multi-year case study of a major multinational, Michael Gibbert points to three different kinds of imaginations and proposes a three-step model for imaginative strategy making.''Introducing new topics on this subject, Strategy Making in a Crisis will strongly appeal to top-level managers, including corporate development departments, and business-unit level strategy. Postgraduate students will also receive ideas for their own theses, not only from the content, but also from the approach - which is deductive and integrates management theories using social science literature - and methodology.'--BOOK JACKET.
Includes bibliographical references (p. 207-221) and index.
Keywords: Strategic planning; Business planning; Crisis management